Reflexions from Evangelii Gaudium - Condori Cutimbo, Raúl (2015)
In this article, the author reflects on the exhortation Evangelii Gaudium, considering the fundamental and important aspects of this document. To this end, he examines the five cores having such exhortation. Similarly, the Pope’s concern on evangelization and the proclamation of Jesus Christ, aspects to be transmitted with the joy of being a believer and with a personal experience with Jesus Christ is emphasized.